2013
DOI: 10.5005/jsd-3-1-25
|View full text |Cite
|
Sign up to set email alerts
|

Zucchellie's Technique with GTR Membrane for Multiple Gingival Recession Coverage

Abstract: Gingival recession associated with dentinal hypersensitivity is one of the commonest issues addressed by the periodontist. The treatment choice for these cases should address biological as well as patient chief complaint. Coronally advanced flaps for root coverage are the most commonly used technique for multiple teeth recessions. This case report describes a case of Class I gingival recession due to faulty brushing technique associate with dentinal hypersensitivity treated with Zucchelli's modification of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…We had only those studies with continuous data outcomes for meta-analysis, and therefore, some studies were excluded as they were reported as dichotomous data types [22,24]. Meta-analysis for pocket depth measurement was done including six studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We had only those studies with continuous data outcomes for meta-analysis, and therefore, some studies were excluded as they were reported as dichotomous data types [22,24]. Meta-analysis for pocket depth measurement was done including six studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, the intervention duration and frequency varied in most studies. In most studies, the intervention time was six months [21][22][23][24][25][26][27]. Two studies had an intervention duration of two months [27,28].…”
Section: Comparisonmentioning
confidence: 99%
See 3 more Smart Citations